Communication Strategies Of Epidemiologists In Disseminating Monkeypox Virus Information - Hasya Azkia Zahra; Tita Melia Milyane (INJECT (Interdisciplinary Journal of Communication), 2025)
This study analyses the communication strategies expert epidemiologists employ in disseminating information about the Monkeypox virus outbreak through mass media. In the context of public health threats such as Mpox (also known as monkeypox), it is essential to understand how to deliver information optimally to shape positive public perception. A qualitative research method with a descriptive approach was used to explore in-depth interviews and observations concerning communication strategies. Informants included expert epidemiologists, media practitioners, communication professionals, and members of the general public. The findings indicate that the information must be grounded in scientifically valid data and trustworthy sources, presented transparently and educationally, and conveyed with empathy in response to public concerns. The use of varied media formats, effective two-way communication, communicator and data credibility, and simplifying complex information for better comprehension are all crucial. The study recommends implementing integrated and responsive health communication strategies to enhance public awareness and engagement in outbreak prevention and control efforts.